Нефротичний синдром - Шеховцева, Тамара Григорівна; Свистун, Сергій Іванович (Запорізький державний медичний університет, 2008)
В статье дано определение нефротического синдрома. В указанной работе подробно изложены его патогенез, клиника, осложнения, приведена классификация. Determination of nephrotic syndrome is given in the article. In the work pathogeny, clinic, complications of nefrotic syndrome, are expounded in detail. Its classification is given.
Keywords: нефротичний синдром; протеїнурія; гіпоальбумінемія; гіперліпідемія; набряки; нефротический синдром; протеинурия; гипоальбуминемия; гиперлипидемия; отеки; nefrotic syndrome; proteinuria; hypoalbuminemia; hyperlipemia; edema